2019
DOI: 10.2134/jeq2016.10.0391
|View full text |Cite
|
Sign up to set email alerts
|

Potential Efficiency of Grassy or Shrub Willow Buffer Strips against Nutrient Runoff from Soybean and Corn Fields in Southern Quebec, Canada

Abstract: Riparian buffer strips (RBS) are encouraged to control agricultural diffuse pollution. In Quebec Province, Canada, a policy promotes 3-m-wide RBS. Abiding farmers minimally maintain herbaceous vegetation, but nutrient retention efficiency could be improved with woody biomass. This work aimed to assess if fast-growing willows (Salix miyabeana Seemen 'SX64') could reduce nutrient loads to a stream, in addition to yielding biomass. Triplicate treatments of two Salix stem densities and a herbaceous control plot we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Several studies explored implications of more active management of the buffer space for diffuse pollution functioning. Hénault‐Ethier et al (2019) found that there was no significant difference in the buffering capacity (for N, P, or K) between 3‐m‐wide riparian zones planted with willow ( Salix spp., regardless of density) and riparian zones with naturally regenerated herbaceous cover. Season strongly affected the buffering ability of the riparian buffer zones, with the highest efficiency occurring when water entering the zone had the highest nutrient concentrations (immediately after sowing and fertilizer application).…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies explored implications of more active management of the buffer space for diffuse pollution functioning. Hénault‐Ethier et al (2019) found that there was no significant difference in the buffering capacity (for N, P, or K) between 3‐m‐wide riparian zones planted with willow ( Salix spp., regardless of density) and riparian zones with naturally regenerated herbaceous cover. Season strongly affected the buffering ability of the riparian buffer zones, with the highest efficiency occurring when water entering the zone had the highest nutrient concentrations (immediately after sowing and fertilizer application).…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 92%
“…Other studies in the collection offer data or discussion on the nutrient offtakes associated with the timber yields. Zak et al (2019) described that, for the IBZ design planted with willow, the standing biomass yields per hectare (after ∼2 yr growth) was 17 to 40 t dry matter, with 8 to 19 t C, 201 to 458 kg N, and 30 to 70 kg P. Hénault‐Ethier et al (2019) assessed whether the inclusion of fast‐growing willow in riparian buffer zones could improve the nutrient retention of the zone. They cited other work that indicated that willow wood harvested after 3 yr from riparian zones allowed for permanent annual export of 116 to 447 kg N ha −1 , 62 to 239 kg K ha −1 , and 23 to 86 kg P ha −1 .…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The second degradation pathway leads to the formation of sarcosine (C 3 H 7 NO 2 ) and inorganic phosphate, through C–P bond cleavage 31–33 . The massive usage of glyphosate in agricultural and non‐agricultural practices has led to the ubiquitous presence of AMPA in the environment 34–38 . However, studies have demonstrated that in industrial and urban areas, AMPA can also be generated by the degradation of both phosphonates and glyphosate present in wastewater 39–41 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a given bioenergy crop production system may not be initially designed with biodiversity support in mind but instead may be designed to enhance biomass production, soil health, or other ecosystem services, such as nutrient loss reduction. For example, willows have commonly been used for phytoremediation, such as vegetative filters and buffers to remove nutrients from wastewater and leachate from agricultural systems [19][20][21][22]. Most of the previous literature on willows and biodiversity, particularly invertebrates, were plantation studies, with the majority of them conducted outside of the U.S. [17].…”
Section: Introductionmentioning
confidence: 99%